1979
DOI: 10.1159/000287387
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymic Feature in Digestive Diseases

Abstract: A comparative study was conducted on the psychological features of chronic pancreatitis, peptic ulcer, ulcerative colitis and the irritable colon syndrome by means of psychological tests and interviews. The patients with irritable colon syndrome were found to be the most neurotic of all, whereas those with the definite type of chronic pancreatitis and ulcerative colitis presented prominent alexithymic characteristics. About one half of the patients having peptic ulcer showed alexithymic features. Despite their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Although these IBS patients were ambulatory, living in the community and continuing with activities of daily living such as employment, they were somewhat more likely to perceive that their QoL was impaired by their condition. The difference between PUD patients and the healthy sample was not significant, a finding also consistent with that of previous research (Nakagawa et al 1979;Whitehead et al 1982).…”
Section: Discussionsupporting
confidence: 92%
“…Although these IBS patients were ambulatory, living in the community and continuing with activities of daily living such as employment, they were somewhat more likely to perceive that their QoL was impaired by their condition. The difference between PUD patients and the healthy sample was not significant, a finding also consistent with that of previous research (Nakagawa et al 1979;Whitehead et al 1982).…”
Section: Discussionsupporting
confidence: 92%
“…Following the introduction of the alexithymia construct, empirical studies initially found IBD patients to be more alexithymic than both psychoneurotic patients [8]and patients with irritable bowel syndrome [9, 10]. The results from these earlier studies are highly questionable, however, as they employed psychometrically weak measures of alexithymia.…”
Section: Introductionmentioning
confidence: 99%
“…Nakagawa et al [13], for example, found IBD patients to be more alexithymic than patients with irrita ble bowel syndrome; however, alexithymia was assessed solely on the basis of clinical interviews and inferences drawn from scores on a personality inventory that assesses a broad range of personality traits. Fava and Pavan [14] also found ulcerative colitis pa tients to be more alexithymic than patients with irritable bowel syndrome and patients with appendicitis; in their study alexithymia was assessed with the observer-rated Beth Is rael Hospital Questionnaire (BIQ), which is of questionable reliability [15].…”
Section: Introductionmentioning
confidence: 99%